Contrast-induced encephalopathy and permanent neurological deficit following cerebral angiography: A case report and review of the literature - Zhang, Yujing; Zhang, Jiancheng; Yuan, Shiying; Shu, Huaqing (Frontiers in Cellular Neuroscience, 2023)
Contrast-induced encephalopathy (CIE) is an uncommon complication associated with contrast exposure during angiographic procedures that is usually transient but occasionally leads to permanent complications or death. Due to the low incidence of CIE, there are still insufficient reports. This study was used to summarize the clinical features of CIE through a case report and systematic review. We summarized and reviewed 127 patients with CIE, and we found that the total incidence of CIE between men and women had no difference (49.61 and 50.39%, respectively), but the average age in female patients with CIE was older than that in male patients (62.19 and 58.77 years, respectively). Interestingly, the incidence of female patients with CIE in the poor prognosis group was significantly higher than that in the good prognosis group (62.50 and 36.51%, respectively), and the average age of these female patients in the poor prognosis group was younger than that in the good prognosis group (61.39 and 62.82 years, respectively). The contrast medium types were mainly nonionic (79.69 and 73.02%, respectively) and low-osmolar (54.69 and 71.43%, respectively) in both groups. Importantly, the total contrast media administrated in patients with poor prognoses was greater than that administrated in patients with good prognoses (198.07 and 188.60 ml, respectively). In addition, comorbidities in both groups included hypertension (55.91%), diabetes mellitus (20.47%), previous contrast history (15.75%), renal impairment (11.81%), and hyperlipidemia (3.15%). The percentage of patients with cerebral angiography was significantly higher in the poor prognosis group than that in the good prognosis group (37.50 and 9.52%, respectively), whereas the percentage of patients with coronary angiography in both groups had the opposite results (35.94 and 77.78%, respectively). In conclusion, CIE may not always have a benign outcome and can cause permanent deficits. Female gender, younger age, the higher dose of contrast medium, and the procedure of cerebral angiography may be related to the patient’s poor prognosis.